SECONDARY PHARMACOLOGICAL PREVENTION OF CARDIOVASCULAR DISEASES: OUR ABILITY IN CLINICAL PRACTICE - E. V. Filippov; S. S. Yakushin (Рациональная фармакотерапия в кардиологии, 2015)
The most pressing issues of the secondary drug prevention of the most common cardiovascular diseases are focused. These are arterial hypertension, stable ischemic heart disease, chronicheart failure.